Pengolahan Tanah Tercemar Logam Berat Pb dan Cd Menggunakan Biochar Sekam Padi dengan Variasi Ukuran Partikel - Harsena Hayas Fika; Shinta Elystia; Aryo Sasmita (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2021)
Soil contamination by heavy metals lead (Pb) and cadmium (Cd) is a form of pollution that is very dangerous for living things. One of the efforts to cultivate polluted soil is the remediation method using biochar from rice husks. The purpose of this study was to analyze the effect of biochar particle size variations on the removal of heavy metals Pb and Cd on contaminated soil. Biochar is made by pyrolysis at 500 0C for 1 hour and flows 0.1 L / minute of N2 gas. This study used a variety of biochar particle sizes of 100 mesh, 60 mesh, 40 mesh and testing time every 10 days for 1 month. The results of this study were the highest Pb and Cd removal in the addition of biochar with a particle size of 100 mesh, namely with a Pb concentration of 91.32 mg / kg and a removal efficiency of 54.05% ; Cd concentration of 10.47 mg / kg and a removal efficiency of 47.36%. Based on the results obtained, it can be stated that the smaller the biochar particle size, the efficiency of heavy metal removal will increase.